THE RELATIONSHIP OF PREGNANT MOTHER'S ANXIETY WITH PARITY DURING THE COVID-19 PANDEMIC - Hana Rosiana Ulfah; Habid Al Hasbi; Emy Kurniawati (LPPM Universitas Duta Bangsa Surakarta, 2022)
Anxiety is an unpleasant feeling dominated by fear. The phenomenon of the current Covid-19 is one of the anxiety factors for pregnant women. This type of research is quantitative with a cross-sectional approach with Chi-Square bivariate test. The research sample on pregnant women was 38 respondents in the Boyolali area. The measuring instrument used is the PASS questionnaire. The results of this study indicate that there is a significant relationship between anxiety in pregnant women and parity with a p-value of 0.001